RANCANG BANGUN SISTEM INFORMASI PENGADAAN SPARE PART MENGGUNAKAN FRAMEWORK CODEIGNITER BERBASIS WEB - Kusariani, Fadila; Fauziyah, Fauziyah; Whendasmoro, Raditya Galih (Jurnal Ilmiah Sistem Informasi, 2023)
Procuring spare parts is an activity process to fulfill or provide needs or supply goods or services under contract or direct purchase to meet needs. Procurement of spare parts is aimed at checking goods, purchasing goods, managing incoming goods, managing stock of goods, and reporting. However, the information system spare parts procurement is still carried out semi-computerized, namely using Microsoft Word and Excel. Based on the problems that occurred a web-based spare parts procurement information system was designed for spare parts procurement using the SDLC method and the design uses the Unified Modelling Language (UML), the spare part procurement information system uses PHP and MySQL, programming languages and to optimize the database uses the CodeIgniter framework